2022
DOI: 10.1097/inf.0000000000003511
|View full text |Cite
|
Sign up to set email alerts
|

Social and Demographic Disparities in the Severity of Multisystem Inflammatory Syndrome in Children

Abstract: Social constructs are known risk factors for multisystem inflammatory syndrome in children. A review of 206 patients demonstrated that children who were non-Hispanic Black, over the age of 12 years or living in a disadvantaged neighborhood associated with severe multisystem inflammatory syndrome in children (intensive care unit admission, intubation and/or vasopressor use).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…Hence, to quantify the effect of ADI on disease severity, it is important to control for race/ethnicity and weight as covariables in the logistic regression analysis. Savorgnan et al studied 206 children with MIS-C in Texas and determined that Non-Hispanic Black race and high ADI to be associated with severe MIS-C. 9 While our study had similar results about the influence of socioeconomic factors on severe disease, we found only non-Hispanic Asian race (in reference to non-Hispanic White) to be associated with severe disease. One of the reasons for this noted discrepancy could be the small number of non-Hispanic Asians in our cohort which may have impacted our results.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Hence, to quantify the effect of ADI on disease severity, it is important to control for race/ethnicity and weight as covariables in the logistic regression analysis. Savorgnan et al studied 206 children with MIS-C in Texas and determined that Non-Hispanic Black race and high ADI to be associated with severe MIS-C. 9 While our study had similar results about the influence of socioeconomic factors on severe disease, we found only non-Hispanic Asian race (in reference to non-Hispanic White) to be associated with severe disease. One of the reasons for this noted discrepancy could be the small number of non-Hispanic Asians in our cohort which may have impacted our results.…”
Section: Discussionsupporting
confidence: 74%
“…3,7 For example, Savorgnan et al in a study of a large cohort of children in Texas, found an increase in odds of severe MIS-C by 21% for each decile increase in ADI. 9 However, this study was limited due to being conducted in a single state and included only those COVID-19 patients with a diagnosis of MIS-C. Hence the study results are not generalizable to other populations and the entire range of severe COVID-19 infections.…”
mentioning
confidence: 98%
“…As many features of MAS overlap with MIS‐C, it was not possible to classify a specific subgroup of patients with MAS in this registry. Of note, although race, ethnicity, and socioeconomic disadvantage have been associated with disproportionately higher rates of MIS‐C (34,35), as well as more severe presentation (36), they were not significant predictors of early anakinra use to suggest that differential cytokine inhibitor use drives disparities in outcomes. Data from our epidemiologic study provide additional evidence to support current ACR recommendations to reserve cytokine inhibitors for treatment intensification in most hospitalized children with MIS‐C.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous study, we found that among patients with multisystem inflammatory syndrome in children, non-Hispanic Black children, older patients, and those living in an area with a high deprivation index were significantly more likely to require intubation and vasoactive support (13). These disparities remained after adjustment for sex, BMI, and vaccination status.…”
Section: Discussionmentioning
confidence: 99%
“…Given the widespread use of pulse oximetry for medical decision-making in this cohort of patients and the increased morbidity in Black symptomatic pediatric patients with COVID-19, these patients may be at risk for worse outcomes. However, the weight of this factor on the outcomes is unknown (2, 7, 13).…”
Section: Discussionmentioning
confidence: 99%